"A desert island is a delightful place": Maria Edgeworth and Robinson Crusoe. Issue 6 (1st November 2020) - Ó Gallchoir, Clíona
ABSTRACT: Maria Edgeworth's response to Robinson Crusoe has been characterized largely negatively, either with reference to the cautions expressed in Practical Education against the spirit of adventure and the encouragement of rash economic speculation, or the critique of primitivism along Crusoesque lines that is found in one of her Moral Tales, "Forester." This essay revises the dominant view of Edgeworth's response to Robinson Crusoe firstly by arguing that the characterization of Edgeworth as "anti-Crusoe" ignores the wide range of references to Defoe's text in her work (in Manoeuvring, Belinda, and Ennui, for example). I argue secondly that an important strand of Edgeworth's response to Crusoe is mediated through her critique of Rousseau, and specifically Rousseau's scepticism as to the value of reading in children's education. Edgeworth's later references to Crusoe, in Patronage and the Sequel to Frank, constitute a rejection of Rousseau's elevation of Robinson Crusoe as a uniquely privileged text, while at the same time acknowledging that "a desert island is a delightful place."